In vitro anti-Mycobacterium tuberculosis activity of some Brazilian Cerrado plants - Pavan, Fernando R. [UNESP]; Sato, Daisy N.; Higuchi, Célio Takashi [UNESP]; Santos, Adolfo C. B. [UNESP]; Vilegas, Wagner [UNESP]; Leite, Clarice Q. E [UNESP] (Sociedade Brasileira de Farmacognosia, 2009)
O objetivo deste trabalho foi realizar uma seleção de algumas plantas de uma determinada região Brasileira com atividade contra Mycobacterium tuberculosis. Extratos clorofórmicos e metanólicos de 37 espécies de plantas distribuídas em 17 famílias do Cerrado Brasileiro foram avaliadas contra M. tuberculosis H37Rv e a Concentração Inibitória Mínima (CIM) foi determinada pelo uso do Microplate Alamar Blue Assay (MABA). Extratos brutos de dezesseis plantas apresentaram valor de CIM < 125 µg/mL e três de 31,2 µg/mL. Estes resultados sugerem que o Cerrado Brasileiro deve possuir um recurso de plantas com constituintes ativos anti-M. tuberculosis que podem ser extraídos por solventes polares e apolares.

The aim of this work was to carry out a screening of some plants of this Brazilian region with activity against Mycobacterium tuberculosis. Chloroform and methanol extracts of 37 plant species distributed among 17 families from Brazilian Cerrado which were tested against M. tuberculosis H37Rv and the Minimum Inhibitory Concentration (MIC) was determined by the use of Microplate Alamar Blue Assay (MABA). Crude extracts from sixteen plants showed MIC value of < 125 µg/mL and three 31.2 µg/mL. These results suggest that the Brazilian Cerrado may be a source of plants that have activity anti-M. tuberculosis constituents that can be extracted by polars and apolars solvents.
Atividade anti-Mycobacterium tuberculosis in vitro de algumas plantas do Cerrado Brasileiro
Keywords: Plantas do Cerrado Brasileiro; Mycobacterium tuberculosis; atividade anti-tuberculose; MABA; Brazilian Cerrado plants; Mycobacterium tuberculosis; antitubercular activity; MABA